Peningkatan Peran Aktif Mahasiswa Pada Kalkulus Integral Menggunakan Metode Pembelajaran Kooperatif Tipe Student Teams-Achievement Division - Sumargiyani, Mrs. (Jurnal Fourier, 2013)
Problems in teaching integral calculus that requires attention in the motivation of learning alongside students is the active role of the student. The active role of the student during the teaching and learning process will affect on the results of his studies. As for the purpose of this research is to improve the students active role by using cooperative learning method type STAD. The subject of research as many as 20 students PGMIPA education courses Math UAD who take Courses Integral Calculus semester three academic year 2012/2013. The cycle is done as much as 3 times the cycle. Data collection is done using sheets of observation, interviewing, documentation, diagnostic tests and field notes. Furthermore the data analyzed by qualitative descriptive. Based on the results of data analysis revealed that the use of cooperative learning methods type STAD can enhance the active role of students in cycle I of 48.53% in category enough, cycle II increased by 59.21% in the category of pretty and cycle III increased by 71.76% in both categories.